ORIENTASI KEWIRAUSAHAAN UNTUK MEMBANGUN KERELASIAN PEMBELI, PEMASOK, PRODUK KOMPLEMENTER DAN IMPLIKASINYA TERHADAP KINERJA BISNIS - Cecep Daryus Darusman (Sainteks: Jurnal Sain dan Teknik, 2019)
This research aimed to examine whether there is the influence of entrepreneurship orientation on relationship with buyers, suppliers, and complementary products and implications on business performance. The research method used is descriptive survey method and explanatory survey with a sample size of 200 respondents, namely entrepreneurs Bandung City Distro. Data analysis method used in this study are SEM (Structural Equation Modeling) with data processing software LISREL 8.30.